Modeling, Methodologies and Tools for Molecular and Nano-scale Communications Modeling, Methodologies and Tools - Suzuki, Junichi; Nakano, Tadashi; Moore, Michael John.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
(Preliminary) The book presents the state of art in the emerging field of molecular and nanoscale communication. It gives special attention to fundamental models, and advanced methodologies and tools used in the field. It covers a wide range of applications, e.g. nanomedicine, nanorobot communication, bioremediation and environmental managements. It addresses advanced graduate students, academics and professionals working at the forefront in their fields and at the interfaces between different areas of research, such as engineering, computer science, biology and nanotechnology.
Part I Fundamentals Of Molecular Communication -- Part II Molecular Communication in Biology -- Part III Electromagnetic-based Nano-scale Communication -- Part IV Nanomaterial and Nanostructure -- Part V Medical Applications of Nanoscale Communication.
Keywords: Microtechnology; Microelectromechanical systems; Computer networks .; Optical materials; Biotechnology; Microsystems and MEMS; Computer Communication Networks; Optical Materials; Biotechnology